Enhanced extractive fermentation for propionic acid production using propioni bacterium acidipropionici immobilized in fibrous red bioreactor and hollow fiber membrane extractors - De Guzman, Lucita (2004)
Usingtraditional fermentation and extraction,propionic acid production was studied with the aim of developing an enhanced extractive fermentation process using propionibacterium acidipropionici (ATCC 4875). Three experimental phases were conducted.
Phase I, conventional fermentation, dealt with the study of recycle fed-batch and recycle batch fermentations using fibrous bed bioreactor (FBB) immobilized with cells of P. acidipropionici for propionic acid production from glucose. Using the recycle fed-batch mode the results showed better final product concentration, yield, ratio and purity and proprionic acid productivity compared to that of the recycle batch.
Phase II, extraction, involved the use of two hollow fiber membrane extractors (HFME) in the simultaneous extraction and separation of propionic acid fromn the mixtures of acids. the reslutts showed that extraction rates increased as pH was decreased and propionic acid and acetic acid concentrationin the feed was increased. Increasing the propionic acid and acetic acid concentration in the feed has no significant effect on the selectivity of the HFME when pH was almost equal to the pKa of the acids. Increased flow rates of the aqueous and solvent phased resulted to high extraction rate.
Phase III, enhanced extractive fermentation, dealt with study and demonstrations of the enhanced recycle batch and recycle feed batch extractive fermentations using FBB and HFME. The recycle batch and recycle feed batch extractive fermentation resulted in better propionic acid concentration, and overall product productivity than the recycle batch extractive fermentation. pH 4.5 was the best pH for the recycle batch extractive fermentation. Ten percent ( 10% (v/v)) amine was the optimum content in the solvent in extractive fermentation to obtain high propionic acid concentration and productivity and faster fermentation than the traditional fermentation (without extraction and using FBB only). Highest extraction of propionic acid was achieved when pH of fermentation broth was less than the pKa of the acid. Process configuration of FBB coupled with HFME is an effective structure in producing propionic acid affording a means of avoiding end product inhibition, reducing solvent toxicity and obtaining maximum propionic acid concentration and overall productivity necessary to minimize cost of investments in bioreactor design.
It is worthwhile to note that lactic acid, which was not reported as one of the byproducts of propionic acid fermentation, was found in the culture broth of P. acidipropionici using HPLC.
Dissertation (PhD Chemical Engineering)-University of the Philippines Diliman)
Keywords: Propionic acid; Propionibacterium